Microfluidics for Greener Flow-Based Colorimetric Analysis of Phosphate and Cinnarizine - Siangdee, Natthaya; Yaemmak, Panumas; Chaohuaimak, Suwimon; Nguyen, Thuan Hoa; Nguyen, Duy Hien; Srisomwat, Chawin; Youngvises, Napaporn (Science & Technology Asia, 2024)
Microfluidic systems are gaining popularity in analytical chemistry owing to their compact size, reduced reagent consumption, and alignment with the principles of green analytical chemistry. In this study, novel microfluidic systems were successfully employed for the determination of phosphate in surface water samples, and cinnarizine in tablet formulations. The three-dimensional lab on a chip (3D LOC) was designed and microfabricated on polymethyl methacrylate (PMMA) in a rectangular figure similar to the conventional flow-through cell. The outstanding is not only a space for the solution to flow through the cell in the spectrophotometer but also a coil for the reaction of sample and reagent to achieve the compact system and enhancement of chemical analysis performance. The 3D LOC was applied for the determination of phosphate in water samples and cinnarizine in tablet dosage forms incorporating the reverse flow injection analysis (r-FIA) with colorimetric detection. The result obtained linear ranges of phosphate is 0.010-2.0 mg P L-1 with an R2 of 0.9985, and those of cinnarizine were 10-150 mg L-1 with an R2 of 0.9963. These designs demonstrated excellent performance characterized by wide linear ranges, low detection limits, and good precision. The proposed microfluidic system holds significant potential to be a greener analytical chemistry.